Analysis of language structure and social relations in religious lecturers' speeches to street food vendors: Pragmatic and sociolinguistic perspectives - Ratri Paramita; Ni Putu Somawati; Muhammad Zulfan (Yayasan Mitra Persada Nusantara, 2025)
This study examines the interplay between language structure and social relations in hierarchical interactions, focusing on the speeches of religious lecturers addressing street food vendors. Using a qualitative approach, the research employs direct observation and audio recordings to capture the linguistic features and social dynamics within these interactions. The data were analyzed through pragmatic and sociolinguistic frameworks to uncover patterns in language use and relational positioning. The findings reveal that religious lecturers utilize distinct linguistic strategies, including simplified language, contextualized examples, and persuasive rhetoric, to engage their audience effectively. Moreover, the social relations within these interactions are characterized by hierarchical, paternalistic, and authority-based dynamics, reflecting broader cultural and societal structures. This study highlights the role of language in shaping power relations and provides insights into the pragmatic and sociolinguistic mechanisms underlying hierarchical communication.